The Preference Survey Module: evidence on social preferences from Tehran - Michael Kosfeld; Zahra Sharafi (Journal of the Economic Science Association, 2023)
We provide evidence on the extent to which survey items in the Preference Survey Module and the resulting Global Preference Survey measuring social preferences—trust, altruism, positive and negative reciprocity—predict behavior in corresponding experimental games outside the original participant sample of Falk et al. (Manag Sci, 2022. https://doi.org/10.1287/mnsc.2022.4455 ). Our results, which are based on a replication study with university students in Tehran, Iran, are mixed. While quantitative items considering hypothetical versions of the experimental games correlate significantly and economically meaningfully with individual behavior, none of the qualitative items show significant correlations. The only exception is altruism where results correspond more closely to the original findings.
Keywords: C81; C83; C90; D01; D03; 330; Preference Survey Module; Global Preference Survey; Validation; Replication; Social preferences